Effects of Socioeconomic Deprivation in Middleand Old-Aged People with Disabilities on Depression in Korea - Yoon, Myeong-Sook; Park, Wan-Kyeong; Kim, Sae-Bom (International Journal of Psychosocial Rehabilitation, 2019)
Despite continuous economic growth, inequality in mental health in Korea is expected to deepen because of socioeconomic polarization and income inequality. This study aimed to identify the diverse types and patterns of socioeconomic deprivation that people with disabilities experience and the relationship between poverty and depression. Data from waves 3 (2007)-13 (2017) of the KoWePS (Korean Welfare Panel Study) were extracted for 12,295 people with disabilities aged 45 or older. For longitudinal data analysis, a generalized least squares fixed model was adopted and performed by fuzzy set theory. Socioeconomic deprivation was examined in six dimensions; deprivation in dietary life, social needs, and health/medicine had major effects on mental health. Socioeconomic deprivation and depression tended to decrease over time. Age, subjective health, and socioeconomic deprivation affected depression changes The study proposed policy and practical intervention plans to build a multidimensional social safety net and enhance mental health.